PIERRE BOURDIEU, SANG JURU DAMAI - Nanang Krisdinanto (Universitas Muhammadiyah Sidoarjo, 2014)
Pierre Bourdieu built his theoretical orientation as a solution to what he saw as a false opposition between objectivism and subjectivism; to quote Bourdieu: “absurd opposition between individual and society”. Bourdieu offered a point of view that emphasizes on duality in the relationship between agent and structure, as an alternative to the previously existing dualistic views. Bourdieu refers to his theoretical orientation as genetic structuralism, constructivist structuralism or structuralist constructivism. Through the concept of habitus, field, and capital, Bourdieu integrated objectivism (which emphasizes the role of objective structure in social practice) and subjectivism (which emphasizes the role of agent in social practice). Bourdieu formulated the theory of social practice with the equation (Habitus x Capital) + Field = Practice. Practice, in Bourdieu’s mind, is the product of the relationship between habitus and field, wherein within field itself there are powers at stake, especially between people with capital and people without capital.